2010
DOI: 10.1002/pssa.200982444
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid functional scheme for defect levels and band alignments at semiconductor–oxide interfaces

Abstract: We introduce a theoretical scheme to study defect energy levels and band alignments at semiconductor–oxide interfaces. The scheme relies on hybrid functionals to overcome the band gap underestimation typically achieved with semilocal density functionals. For atomically localized defects, the more accurate description achieved with hybrid functionals does not lead to significant shifts of the charge transition levels, provided these levels are referred to a common reference potential. This result effectively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
(91 reference statements)
2
8
0
Order By: Relevance
“…Conesa [28] used instead the experimental dielectric constant. Other authors proposed adjusting α so as to reproduce the experimental band gap of materials [18,29,30], aiming at testing how the functional performs in predicting different electronic features, such as band edge positioning at semiconductor interfaces and defect energy levels in solids. Concerning the last point, Chen and Pasquarello [31] showed that good results are obtained if the parameter α is chosen in such a way that the modified hybrid functional matches the computed GW band gap of the intrinsic material.…”
Section: Introductionmentioning
confidence: 99%
“…Conesa [28] used instead the experimental dielectric constant. Other authors proposed adjusting α so as to reproduce the experimental band gap of materials [18,29,30], aiming at testing how the functional performs in predicting different electronic features, such as band edge positioning at semiconductor interfaces and defect energy levels in solids. Concerning the last point, Chen and Pasquarello [31] showed that good results are obtained if the parameter α is chosen in such a way that the modified hybrid functional matches the computed GW band gap of the intrinsic material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hybrid density functions based on the semi-local PBE approximation were implemented. To correct the underestimated bandgap, 35% of PBE exchange was replaced with the exact one [27]. To identify the band edge shift with the change of the Al doping level, the average electrostatic potential (AEP) was calculated and aligned to the vacuum level which was scaled to 0 V. The VBM and conduction band minimum (CBM) were consequently aligned to the AEP based on the band diagram [28].…”
Section: Resultsmentioning
confidence: 99%
“…45 These modifications of the HF exchange fraction of hybrid DFT functionals are particularly useful to investigate interfaces, band offsets, and defect levels. 19,46 In our methodologies, HF exchange fractions introduced into the screened HF exchange potential and Slater-formula are changed at the atomic scale and automatically determined through the SCF loop. The new position-dependent atomic dielectric constant approach may be useful for systems that are beyond the scope of this manuscript, such as interfaces and band offsets.…”
Section: Resultsmentioning
confidence: 99%